PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN RUMAH MAKAN MBAH JINGKRAK DI JAKARTA - Susilowati, Tri Yuni (E-journal Widya Non-Eksakta, 2019)
Mbah Jingkrak Restaurant is one of the many restaurants that have been established in Jakarta. At present there are around 16 branches spread across various regions in Indonesia. Mbah Jingkrak Restaurant is a development of Bentuman restaurant which specializes in selling Steak and has been modified with Javanese tongue. Mbah Jingkrak Restaurant was originally established in the city of Semarang on Jl. Banyan no. 3 on September 1, 2005. The purpose of this study was to analyze the 7 Ps marketing mix factor that influenced customer satisfaction with the services provided by Mbah Jingkrak Restaurant and analyzed customer loyalty towards Mbah Pingkrat Restaurant in Jakarta. This research uses Structural Equation Modeling (SEM) Analysis. To determine the effect of price factors (place), place (place), menu (product), physical evidence (physical evidence), promotion (promotion) and employees (people) on customer satisfaction and loyalty. The sample in this research object is visitors who visit the outlets that are used as research objects. This research uses quota sampling technique which is included in proposive sampling. The results of the analysis of the seven marketing mixes that most significantly affect satisfaction are menu and employee factors. Based on the results of satisfaction analysis Mbah Jingkrak Restaurant is in the category of satisfaction and customer loyalty Mbah Jingkrak Restaurant is in the Loyal category.